Congenital myopathies: Natural history of a large pediatric cohort. (6th January 2015) - Colombo, Irene; Scoto, Mariacristina; Manzur, Adnan Y.; Robb, Stephanie A.; Maggi, Lorenzo; Gowda, Vasantha; Cullup, Thomas; Yau, Michael; Phadke, Rahul; Sewry, Caroline; Jungbluth, Heinz; Muntoni, Francesco
Abstract : Objective: To assess the natural history of congenital myopathies (CMs) due to different genotypes. Methods: Retrospective cross-sectional study based on case-note review of 125 patients affected by CM, followed at a single pediatric neuromuscular center, between 1984 and 2012. Results: Genetic characterization was achieved in 99 of 125 cases (79.2%), with RYR1 most frequently implicated (44/125). Neonatal/infantile onset was observed in 76%. At birth, 30.4% required respiratory support, and 25.2% nasogastric feeding. Twelve percent died, mainly within the first year, associated with mutations in ACTA1, MTM1, or KLHL40 . All RYR1 -mutated cases survived and did not require long-term ventilator support including those with severe neonatal onset; however, recessive cases were more likely to require gastrostomy insertion ( p = 0.0028) compared with dominant cases. Independent ambulation was achieved in 74.1% of all patients; 62.9% were late walkers. Among ambulant patients, 9% eventually became wheelchair-dependent. Scoliosis of variable severity was reported in 40%, with 1/3 of (both ambulant and nonambulant) patients requiring surgery. Bulbar involvement was present in 46.4% and required gastrostomy placement in 28.8% (at a mean age of 2.7 years). Respiratory impairment of variable severity was a feature in 64.1%; approximately half of these patients required nocturnal noninvasive ventilation due to respiratory failure (at a mean age of 8.5 years). Conclusions: We describe the long-term outcome of a large cohort of patients with CMs. While overall course is stable, we demonstrate a wide clinical spectrum with motor deterioration in a subset of cases. Severity in the neonatal/infantile period is critical for survival, with clear genotype-phenotype correlations that may inform future counseling.